ELABORATION OF HEATSTROKE IN INDONESIA - Amelia, Meilany; Tosepu, Ramadhan (Universitas Halu Oleo, 2024)
ABSTRACT This review article discusses how heat stress can impact persons who work outside or indoors with poor air quality, and how it can lead to medical concerns. Heat-related illness (HRI) is a complaint or clinical sickness caused by the body's inability to control its internal temperature as a result of excessive heat exposure and inadequate heat removal. There are several types of heat-related diseases, ranging from mild symptoms like heat edema, heat rush, and heat cramps to more serious problems like heat exhaustion and deadly scenarios like heart attack, which is a medical emergency. Numerous risk factors, such as the physical, chemical, biological, physiological, and psychological conditions of the personnel and their environment, might exacerbate this predicament. Heatstroke is the most serious form of heat-related illness, characterized by a body temperature of greater than 40°C and a diagnosis of nervous system failure. Internal and external factors impact the risk of heatstroke. The aim of this research is to describe health and safety concerns, as well as illnesses and heatstroke. A descriptive design and a literature review approach are used in this study. The papers for this review were obtained from the journal databases PubMed and Google Scholar. Based on the articles analyzed in the literature. Extreme heat can harm internal organs, causing heart muscle cell and blood artery collapse, organ damage, and death, it is possible to infer that basic knowledge on heatstroke must be provided in order to avoid illness or problems with health and safety in everyday life. Keyword: Elaborate, Heatstroke, Indonesia, Knowledge